PENAMBAHAN RIMPANG JAHE (Zingiber officinale ) DAN LAMA PENYIMPANAN TERHADAP MUTU PINDANG KEMBUNG - Ako, Jamaludin (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2016)
The purpose of this study was to determine the effects of additional red ginger rhizome and shelf life to the quality of mackerelfish boiled bloating. The results of research showed that the additional of red ginger rhizome and shelf life gave very significant effects on the organoleptic assessment of color and water levels. The best interaction treatment was the treatment of 40% addition of red ginger rhizome and without shelf life amounted to 4,22 color of organoleptic properties (like) and water levels 42,74%. The best partial treatment of red ginger rhizome was the additional of 40% red ginger rhizome with the organoleptic properties of color 3,02 (somewhat like), aroma 3,31 (somewhat like), texture 3,29 (somewhat like), taste 3,02 (somewhat like), water levels 53,63% and total microbes of 5,03 CFU/g. The best partial treatment of self life was at without shelf life with 4,14 color af organoleptic properties (like), aroma 4,34 (like), texture 4,38 (like), taste 4,19 (like), water levels 43,74%, protein levels 24,43 and total microbes of 3,74 x 102 CFU/g. Key Words : boiled fish, mackerelfish, red ginger rhizome, shelf life.